2014
DOI: 10.3791/51734
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Integrated Anaerobic Digestion and Hydrothermal Carbonization for Bioenergy Production

Abstract: Lignocellulosic biomass is one of the most abundant yet underutilized renewable energy resources. Both anaerobic digestion (AD) and hydrothermal carbonization (HTC) are promising technologies for bioenergy production from biomass in terms of biogas and HTC biochar, respectively. In this study, the combination of AD and HTC is proposed to increase overall bioenergy production. Wheat straw was anaerobically digested in a novel upflow anaerobic solid state reactor (UASS) in both mesophilic (37 °C) and thermophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…110 Similarly, Reza et al (2014) showed that the combination of AD and HTC processes yielded 13.2 MJ kg À1 DM initial feedstock, representing at least 20% and 60.2% more than for HTC and AD alone, respectively. 114 Recently, Funke et al (2013) compared the performance of vapothermal carbonization (VTC) and traditional HTC processes on anaerobic digestate. 115 VTC was carried out with a higher initial solid content (25%) compared to HTC (5%), as the biomass was subjected to saturated steam instead of liquid water.…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…110 Similarly, Reza et al (2014) showed that the combination of AD and HTC processes yielded 13.2 MJ kg À1 DM initial feedstock, representing at least 20% and 60.2% more than for HTC and AD alone, respectively. 114 Recently, Funke et al (2013) compared the performance of vapothermal carbonization (VTC) and traditional HTC processes on anaerobic digestate. 115 VTC was carried out with a higher initial solid content (25%) compared to HTC (5%), as the biomass was subjected to saturated steam instead of liquid water.…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…Lower temperature hydrothermal process waters typically have higher biodegradability than higher temperature process waters [48][49][50]. An assessment of experimental biochemical methane potential (BMP) has been performed by many, although the majority of studies have focused on sewage sludge [51][52][53][54][55][56][57], only limited studies are available for digestate from other feedstocks [48,[58][59][60] and there is an absence of BMP studies for process waters from woody or lignocellulosic biomass. There are potential benefits for blending digestate with other feedstocks containing lignocellulosic biomass as this may increase the calorific value of the resulting hydrochar and allow more recalcitrant biomass to be treated for biogas generation.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant compound in the HTC effluent, namely acetic acid, has not been detected in the permeate when these cascades were used (Table 4), which seems beneficial from the point of view of the use of retentate in the AD since volatile fatty acids are consumed during the acetogenesis [94], which is one of the main stages of AD process [95,96]. From the water-recovery perspective, especially in the context of its potential use in the agriculture, presence of acetic acid could be considered somewhat problematic as it is included on lists of pesticides, e.g., Pesticide Screening List for Luxembourg [97].…”
Section: Resultsmentioning
confidence: 99%